Enhancement of Quality of Learning through Material Presentation based on Multimedia in Barrang Lompo Island (Peningkatan Kualitas Pembelajaran melalui Penyajian Materi Berbasis Multimedia di Pulau Barrang Lompo) - Intan, Indo (Jurnal Pekommas, 2016)
One of the main factors the low quality of human resources in education is learning depends on conventional methods which result in low quality of learning. This study aims to improve softskill and hardskill for teachers to enable them to manage quality learning based multimedia to produce students whom have basic competencies. The research method through four phases: assessment, training, learning, and evaluation. Data obtained through the assessment of the student to teachers, the assessment media experts to the teachers, and the assessment of student to teacher results by taking a sample of 7 teachers and 10 students. At Alfa Testing obtained an increase of indicators on aspects of the learning content, learning techniques, and learning outcomes including very good category. Gain testing showed that the presentation of learning material based multimedia including high category. Hypothesis testing showed that the presentation of material based on multimedia in all three aspects can improve the quality of learning.Salah satu faktor utama rendahnya kualitas sumber daya manusia bidang pendidikan adalah pembelajaran masih menggunakan metode konvensional yang berakibat pada rendahnya kualitas pembelajaran. Kajian ini bertujuan untuk menambah pengetahuan dan keterampilan bagi guru agar mereka mampu mengelola pembelajaran yang berkualitas berbasis multimedia untuk menghasilkan luaran siswa yang memiliki kompetensi dasar. Metode pelaksanaan kegiatan ini melalui empat tahapan: penjajakan, pelatihan, pembelajaran, dan evaluasi. Data diperoleh melalui hasil penilaian guru terhadap siswa, hasil penilaian tim ahli terhadap guru, dan hasil penilaian siswa terhadap guru dengan mengambil sampel 7 orang guru dan 10 orang siswa. Pada Alfa Testing diperoleh peningkatan indikator capaian pada aspek konten, teknik, dan luaran pembelajaran dengan kategori Sangat Baik. Gain Testing menunjukkan bahwa penyajian pembelajaran berbasis multimedia termasuk kategori Tinggi. Hypothesis Testing menunjukkan bahwa penyajian materi berbasis multimedia pada ketiga aspek dapat meningkatkan kualitas pembelajaran.